Health Services for the Elderly in the Perspective of Law Number 13 of 1998 concerning the Welfare of the Elderly - Indira Khanza Pramandani; Yogie Fadly Salihi; Odang Suparman (Jurnal Ilmiah Dunia Hukum, 2025)
This study aims to analyze the implementation of Law Number 13 of 1998 on the Welfare of the Elderly in fulfilling elderly health rights in Indonesia. Based on the Preamble to the 1945 Constitution and Article 28C, the state is obligated to improve the welfare of all citizens, including the growing elderly population that is projected to make Indonesia an aging society. This research employs a normative qualitative method with conceptual, comparative, and literature review approaches, examining legal regulations, scholarly works, and international instruments such as CEDAW and CRPD. The findings show that the law regulates elderly rights to comprehensive healthcare, government and community roles, priority for vulnerable groups, funding mechanisms, and social protection through BPJS Kesehatan. However, implementation challenges remain, including disparities in healthcare access, limited funding, and low awareness. The discussion highlights derivative programs such as Elderly Posyandu, geriatric services, and medical rehabilitation, though their reach is uneven. The study concludes that while the legal framework is adequate, stronger policies, better budgeting, and improved public education are needed. Recommendations include expanding community-based health programs, enhancing geriatric training, and strengthening multi-stakeholder collaboration to support active aging.